An Analysis of Bank Syariah Indonesia Digitalization - Tiara, Elsa; Achmad, Dliyaudin; Bin Nasarruddin, Razie (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2023)
The purpose of this research is to explain how digitalization is happening in Islamic banking, especially Indonesian Islamic Banks. This research method uses a descriptive qualitative approach by describing and analyzing the data obtained. This research model uses character study research that is based on the personality or individual of a character who is considered to have an important role or special event that is written. The results of this research are that Islamic banking, especially Bank Syariah Indonesia, has taken advantage of increasingly sophisticated technological developments by creating digital-based services and products. One of the digital services available at Bank Syariah Indonesia is the BSI Mobile application. BSI Mobile application provides a variety of banking transaction features, including Cardless cash withdrawal service.